2016
DOI: 10.1016/j.ijer.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a sociocultural approach to understanding academic self-concept in twice-exceptional students

Abstract: This article explores a sociocultural approach to gaining a deeper understanding of academic self-concept by twice-exceptional students. Academic self-concept is a multidimensional, psychological construct, critical in identify formation. Twiceexceptional students are students who are gifted with a coexisting disability that affects learning. A theoretical framework is presented based on interactions within a theorised zone of proximal development using case-study methodology. Data are analysed according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…It remains to be seen what has been problematic within socio-cultural studies that studied the language to know how to avoid it or, at least, how to minimize its impact. A number of researches show that the number of people participating in the studies was limited (Escotto, 2011, Roth and Gardener, 2012, Goncalves Teixeira, 2014, Townend and Brown, 2016. However, the research limitations on population discovered by the quality of deepening studies and their specific features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be seen what has been problematic within socio-cultural studies that studied the language to know how to avoid it or, at least, how to minimize its impact. A number of researches show that the number of people participating in the studies was limited (Escotto, 2011, Roth and Gardener, 2012, Goncalves Teixeira, 2014, Townend and Brown, 2016. However, the research limitations on population discovered by the quality of deepening studies and their specific features.…”
Section: Discussionmentioning
confidence: 99%
“…Practices such as schooling generate specific products or learning which the literature review confirmed. Townend and Brown (2016) studied the understanding of the self-concept in excellent students. These cases are very valid to the study of language from a sociocultural perspective.…”
Section: Participation In Practicementioning
confidence: 99%
“…A learner-oriented perspective is prominent in the use of assessment methods, but at the same time, student influence on assessment is perceived as low in both countries [9]. Assessment is essential to determine competence, motivate, and see aspects of learning that students have mastered [10]. Assessment will determine the value of something (goals, activities, decisions, performance, processes, people, objects, and more.)…”
Section: Assessmentmentioning
confidence: 99%
“…Muchas de las investigaciones muestran como limitación la escasa cantidad de personas que participaban de los estudios (Escotto, 2011;Roth y Gardener, 2012;Goncalves Teixeira, 2014;Townend y Brown, 2016; entre otros). Sin embargo, aún se puede sostener que lo que carecen en cantidad de la población lo tienen en la calidad de la profundización y la especialidad del tipo de características particulares que poseen.…”
Section: Conclusionesunclassified